Lead bismuth / supercritical carbon dioxide uniform corrosion and grain boundary oxidation resistant austenitic stainless steel and method of making

A novel austenitic stainless steel was prepared by optimizing the alloy composition and heat treatment process, which solved the corrosion problem in the high-temperature lead-bismuth/supercritical carbon dioxide environment, and achieved long-term stability and resistance to grain boundary oxidation. It is suitable for lead-bismuth cooled reactor-supercritical carbon dioxide Brayton cycle system.

CN119307832BActive Publication Date: 2026-11-06SHANGHAI JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411198220.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2026-11-06
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

Existing materials cannot maintain long-term stability in high-temperature lead-bismuth/supercritical carbon dioxide environments. They exhibit high corrosion rates, preferential oxidation at grain boundaries, and penetration, leading to material failure and failing to meet the service requirements of lead-bismuth reactors/supercritical carbon dioxide Brayton cycle systems.

Method used

By rationally designing the composition of a new type of austenitic stainless steel, which includes nickel, chromium, aluminum, manganese, silicon, niobium, yttrium and iron, and using vacuum induction furnace melting, refining and heat treatment processes, austenitic stainless steel with excellent corrosion resistance is prepared, ensuring that the oxide film thickening is small and there is no preferential intergranular oxidation at high temperatures.

Benefits of technology

At a high temperature of 650℃, the oxide film thickness of the new austenitic stainless steel in lead-bismuth is less than 6.5μm, and the oxidation weight gain in supercritical carbon dioxide is less than 150 mg/dm2. No obvious preferential oxidation at grain boundaries occurs, which meets the requirements for long-term service.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307832B_ABST
    Figure CN119307832B_ABST
Patent Text Reader

Abstract

This invention discloses an austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation in lead-bismuth / supercritical carbon dioxide environments, and its preparation method. The alloy composition, by mass fraction, comprises 12-20% nickel, 10-20% chromium, 1.5-4.5% aluminum, 1-4% manganese, 0.5-1% silicon, 0.5-1% niobium, 0-0.1% yttrium, and 0.02-0.1% carbon, with the balance being Fe. It exhibits strong corrosion resistance and resistance to preferential intergranular oxidation in lead-bismuth and supercritical carbon dioxide environments. The austenitic stainless steel prepared by this invention shows minimal corrosion weight gain, minimal surface oxide film thickening, and shallow grain boundary oxidation depth in high-temperature (450-650℃) lead-bismuth and supercritical carbon dioxide service environments, demonstrating high corrosion resistance and resistance to preferential intergranular oxidation corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alloys, specifically relating to a novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation, and its preparation method. Background Technology

[0002] The current range of materials available for supercritical carbon dioxide Brayton cycle systems primarily comes from supercritical and ultra-supercritical thermal power plants and high-temperature, high-pressure chemical equipment, mainly ferritic / martensitic steel (F / M steel), (super) austenitic stainless steel, and nickel-based alloys. Existing research results show that F / M steel exhibits significant corrosion weight gain and oxide film thickening under supercritical carbon dioxide conditions. Under the same temperature and pressure conditions, the corrosion rate of austenitic stainless steel and nickel-based alloys is much lower than that of F / M steel. Under long-term supercritical carbon dioxide corrosion, the Cr-rich oxide film formed on the surface of high-Ni, high-Cr austenitic stainless steel and nickel-based alloys will peel off and cannot maintain long-term stability. In a lead-bismuth environment, F / M steel has weaker resistance to oxidation corrosion compared to austenitic stainless steel; while for austenitic stainless steel and nickel-based alloys, the main constituent elements Ni and Cr in the material matrix have high solubility in lead-bismuth, especially Ni, which undergoes selective dissolution in lead-bismuth, causing severe lead-bismuth infiltration into the matrix and leading to material failure. Patent CN113151747A discloses an aluminum-containing austenitic stainless steel that maintains excellent thermal and chemical stability in high-temperature supercritical media. However, the Ni content (15-30%) in this patent design is relatively high, and it lacks resistance to long-term oxidation and dissolution corrosion in high-temperature lead-bismuth environments. Therefore, for heat exchangers in lead-bismuth reactor / supercritical carbon dioxide Brayton cycle systems with a target service life of 20-30 years, there are currently no candidate materials that can meet this requirement.

[0003] In addition, austenitic stainless steel often undergoes severe preferential grain boundary oxidation in high-temperature corrosive environments. As a key precursor in the stress corrosion cracking process, this phenomenon generally occurs at the crack tip, inducing element diffusion and grain boundary migration, thus exacerbating stress corrosion cracking. Numerous studies have shown that the dissolution and oxidation corrosion of (15-18)Cr-(10-15)Ni austenitic stainless steel in high-temperature lead-bismuth environments is significantly aggravated at random large-angle grain boundaries and twins. Among these, preferential intergranular oxidation leads to cracking at the grain boundaries, allowing lead-bismuth to penetrate and further detach the oxide film and matrix. In supercritical carbon dioxide environments, preferential intergranular oxidation also occurs on the corrosion surface of austenitic stainless steel. Under stress loading conditions, vacancy accumulation occurs, resulting in the formation of numerous voids at the grain boundaries, which reduces the material's resistance to stress corrosion cracking and may couple with mechanisms such as carburization and creep, leading to grain boundary degradation and accelerated material failure. Currently, there are no candidate materials that can resist preferential intergranular oxidation corrosion in high-temperature lead-bismuth / supercritical carbon dioxide corrosion environments. Therefore, it is necessary to focus on the mechanism of grain boundary oxidation and to prepare novel austenitic stainless steel materials with excellent resistance to grain boundary oxidation corrosion through composition design. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0005] In view of the problems existing in the above and / or prior art, the present invention is proposed.

[0006] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation, characterized in that: the novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation contains nickel, chromium, aluminum, manganese, silicon, niobium, yttrium, carbon and iron; The composition, by mass percentage of raw materials, is as follows: nickel 12-20%, chromium 10-20%, aluminum 1.5-4.5%, manganese 1-4%, silicon 0.5-1%, niobium 0.5-1%, yttrium 0-0.1%, carbon 0.02-0.1%, with the balance being Fe.

[0008] As a preferred embodiment of the preparation method described in this invention, the raw materials contain the following components by mass percentage: nickel 18%, chromium 14%, aluminum 3.5%, manganese 2%, silicon 0.6%, niobium 0.6%, yttrium 0.08%, carbon 0.04%, with the balance being Fe.

[0009] As a preferred embodiment of the preparation method described in this invention, the novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation also possesses the following characteristics: (i) The oxide film thickness increased by less than 6.5 μm after 500 hours in lead-bismuth at 650 °C; (ii) The weight gain after oxidative stress in supercritical carbon dioxide at 650℃ for 500 hours is less than 150 mg / dm2; (iii) No obvious preferential oxidation of grain boundaries occurred after 500 hours in supercritical carbon dioxide at 650℃.

[0010] (iv) No obvious preferential oxidation of grain boundaries occurred in the lead-bismuth eutectic alloy with saturated oxygen concentration at 650℃ for 500 hours.

[0011] Another objective of this invention is to overcome the shortcomings of the prior art and provide a novel method for preparing austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation. As a preferred embodiment of the preparation method described in this invention, the pure metal raw materials Fe, Cr, Ni, Nb, and Y are thoroughly mixed according to the designed composition in a vacuum induction furnace and then placed in a crucible for vacuuming and electric melting. During the melting process, the high vacuum environment and low melting rate are used to enhance the efficiency of carbon deoxidation and nitrogen removal. After the steel is liquefied and cleaned, C and Al are added and fully melted before refining. After refining, argon gas is introduced into the induction furnace, and Si and Mn are added to further reduce the oxygen and sulfur content, and then it is cast into steel ingots. After smelting, the steel ingot is forged into shape, and after forging, it is air-cooled to obtain a stainless steel forging billet, which is then polished to remove the oxide scale. A new type of austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation is obtained by heat treatment of stainless steel forging billets with oxide scale removed.

[0012] As a preferred embodiment of the preparation method described in this invention, the steel ingot is placed in a heating furnace during the forging process and heated to 1200°C at a heating rate of 120°C / h, held for 3-8 hours, and then forging begins. The final forging temperature is not lower than 925°C, and the stainless steel billet is obtained by water cooling or air cooling after forging.

[0013] As a preferred embodiment of the preparation method described in this invention, the refining conditions are: holding at 1500°C for at least 10 minutes.

[0014] As a preferred embodiment of the preparation method described in this invention, the heat treatment conditions are as follows: the stainless steel forging billet is solution treated at 1100~1200℃ for 60-120 minutes, water cooled, and then aged at 650-700℃ for 100 hours.

[0015] As a preferred embodiment of the preparation method described in this invention, the vacuum electric melting conditions are 1550~1800℃ and the electric power is 5~40KW.

[0016] As a preferred embodiment of the preparation method described in this invention, the initial forging temperature is not lower than 1150℃ and not higher than 1245℃, and the final forging temperature is 900~1050℃.

[0017] Another objective of this invention is to overcome the shortcomings of the prior art and provide a novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation for use in heat exchangers of supercritical carbon dioxide Brayton cycle power systems for lead-bismuth cooled fast reactors.

[0018] Beneficial effects of this invention: (1) This invention addresses the corrosion-resistant service material requirements of lead-bismuth cooled reactor-supercritical carbon dioxide Brayton cycle heat exchange system. Through reasonable composition design, the content and ratio of each element in the alloy are adjusted, and heat treatment and other processes are used to obtain a new type of aluminum-containing austenitic stainless steel. This material has the ability to resist high-temperature lead-bismuth and supercritical carbon dioxide corrosion.

[0019] (2) The novel austenitic stainless steel of this invention has good high-temperature corrosion resistance and resistance to preferential intergranular oxidation corrosion. In lead-bismuth at 650℃, the oxide film thickness increased by less than 6.5 μm after 1000 hours, and no obvious preferential intergranular oxidation corrosion behavior occurred. In supercritical carbon dioxide at 650℃, the oxidation weight gain was less than 130 mg / dm³ after 1000 hours. 2 It can meet the corrosion resistance requirements of lead-bismuth eutectic alloys at 450-650℃ or materials in supercritical carbon dioxide environments at 450-650℃ and 20MPa. Attached Figure Description

[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 Corrosion weight gain curves of AFA steel provided for embodiments of the present invention and 316LN of Comparative Example 1 in supercritical carbon dioxide at 650°C for 1000 h.

[0021] Figure 2 The corrosion cross-sectional morphology characterization results of AFA steel provided in the embodiments of the present invention and 316LN of Comparative Example 1 in saturated oxygen concentration lead bismuth at 650°C for 1000h.

[0022] Figure 3 Statistical results of the corrosion degree of AFA steel provided in the embodiments of the present invention and 316LN of Comparative Example 1 in saturated oxygen concentration lead bismuth at 650°C for 1000h. Detailed Implementation

[0023] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0024] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0026] Unless otherwise specified, all raw materials used in the embodiments of this invention are commercially available.

[0027] Example 1 This invention provides a novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation, suitable for heat exchangers in supercritical carbon dioxide Brayton cycle power systems with lead-bismuth cooled fast reactors, and its preparation method: The composition by mass fraction includes the following components: 18% Ni, 14% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 3.5% Al, 0.08% Y, with the balance being Fe.

[0028] (1) Pure metal raw materials Fe, Cr, Ni, Nb and Y are mixed in a vacuum induction furnace and placed in a crucible for vacuuming and electric melting. The melting temperature is 1500℃ and the holding time is not less than 10 minutes. After the steel is liquefied and cleared, C and Al are added and fully melted before refining.

[0029] (2) After refining, 0.04 MPa argon gas is introduced into the induction furnace, and Si and Mn are added to further reduce the oxygen and sulfur content. Then it is cast into steel ingots.

[0030] (3) The steel ingots after smelting are formed by forging. During the forging process, the steel ingots are placed in a heating furnace and heated to 800°C at a heating rate of 100°C / h for 1-2 hours. Then, the temperature is increased to 1200°C at a heating rate of 100°C / h and held for 3 hours. Then, the temperature is reduced to 1180°C and held for 1 hour before forging begins. The initial forging temperature is not lower than 1180°C and not higher than 1250°C. The final forging temperature is 950~1000°C. The stainless steel forging billet is obtained by air cooling and then polished to remove the oxide scale.

[0031] The heat treatment process is as follows: the stainless steel forging billet is solution treated at 1150℃ for 60 minutes, water cooled, and then aged at 650℃ for 100 hours.

[0032] Example 2 The difference from Example 1 is that, by mass fraction, it contains 18% Ni, 14% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 3.5% Al, 0.05% Y, with the balance being Fe.

[0033] The heat treatment process is as follows: the stainless steel forging billet is solution treated at 1135℃ for 60 minutes, water cooled, and then aged at 650℃ for 100 hours.

[0034] Example 3 The difference from Example 1 is that, by mass fraction, it contains 18% Ni, 14% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 2.5% Al, 0.08% Y, with the balance being Fe.

[0035] The heat treatment process is as follows: the stainless steel forging billet is solution treated at 1125℃ for 60 minutes, water cooled, and then aged at 650℃ for 100 hours.

[0036] Example 4 The difference from Example 1 is that, by mass fraction, it contains 18% Ni, 14% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 3.5% Al, 0.08% Y, with the balance being Fe.

[0037] The heat treatment process is as follows: the stainless steel forging billet is solution treated at 1140℃ for 60 minutes, water cooled, and then aged at 650℃ for 100 hours.

[0038] Comparative Example 1 The difference from Example 1 is that, by mass fraction, it contains 13% Ni, 18% Cr, 2% Mn, 1% Si, 0.0035% C, with the balance being Fe.

[0039] Comparative Example 2 The difference from Example 1 is that, by mass fraction, it contains 18% Ni, 14% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 1.5% Al, 0.08% Y, with the balance being Fe.

[0040] Comparative Example 3 The difference from Example 1 is that, by mass fraction, it contains 18% Ni, 14% Cr, 2% Mn, 0.2% Si, 0.6% Nb, 0.04% C, 2.5% Al, 0.08% Y, with the balance being Fe.

[0041] Comparative Example 4 The difference from Example 1 is that, by mass fraction, it contains 16% Ni, 14% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 2.5% Al, 0.08% Y, with the balance being Fe.

[0042] Comparative Example 5 The difference from Example 1 is that, by mass fraction, it contains 18% Ni, 16% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 2.5% Al, 0.08% Y, with the balance being Fe.

[0043] Comparative Example 6 The difference from Example 1 is that, by mass fraction, it contains 18% Ni, 16% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 2.5% Al, 0.2% Y, with the balance being Fe.

[0044] The ingredients are shown in Table 1.

[0045] Table 1 (Unit: Percentage by Mass)

[0046] Corrosion tests were conducted on Examples 1-4 and Comparative Examples 1-6 in high-temperature lead-bismuth (650°C, saturated oxygen concentration) and supercritical carbon dioxide (650°C, 20MPa). The corrosion resistance of the design scheme was evaluated by the weight gain due to supercritical carbon dioxide corrosion and the thickening of the oxide film in the lead-bismuth environment. The resistance to preferential intergranular oxidation of the design scheme was evaluated by the grain boundary oxidation depth. The results are as follows.

[0047] Figure 1The corrosion weight gain curves of AFA steel and comparative examples provided in the embodiments of the present invention in supercritical carbon dioxide at 650℃ for 1000 h are shown. The results indicate that Examples 1-4 have smaller corrosion weight gain compared to Comparative Examples 1-6, indicating that the material has strong resistance to supercritical carbon dioxide corrosion, and the formed oxide film has strong protective properties, preventing further oxidation and weight gain. Comparative Examples 1, 2, and 3 show increased corrosion weight gain compared to the examples, indicating that lower Al and Si contents than the designed composition lead to a significant reduction in the protective properties of the oxide film. Comparative Examples 1, 4, and 5 show increased corrosion weight gain compared to the examples, indicating that lower Ni and Cr contents are detrimental to the formation of a protective Cr and Al oxide film, reducing the material's corrosion resistance. Examples 2, 3, 4, and 6 show higher corrosion weight gain compared to Example 1, indicating that doping with a reasonable amount (0-0.1%) of Y element has a positive effect on the material's resistance to supercritical carbon dioxide corrosion.

[0048] Figure 2 The corrosion cross-sectional morphology characterization results of AFA steel and comparative examples provided in the embodiments of the present invention in 650℃ saturated oxygen concentration lead-bismuth for 1000h are presented. The results show that Examples 1-4 have the thinnest oxide film, indicating that this oxide film has the best protective properties, can prevent further corrosion of the material matrix by lead-bismuth, has strong resistance to lead-bismuth corrosion, does not undergo preferential intergranular oxidation, and has strong grain boundary oxidation resistance. Comparative Examples 1, 2, and 3 show that Al and Si have a positive effect on the protective properties of the oxide film. Comparative Examples 1, 4, and 5 show that a decrease in Ni and Cr content is not conducive to the formation of a protective Cr and Al oxide film, leading to a decrease in the protective properties of the oxide film, an increase in the degree of internal oxidation, and a decrease in the material's resistance to lead-bismuth corrosion. A comparison of Examples 1-4 and Comparative Example 6 shows that doping with a reasonable amount (0-0.1%) of Y element has a positive effect on the material's resistance to lead-bismuth corrosion.

[0049] Figure 3 The statistical results of the corrosion degree of AFA steel provided in the embodiments of the present invention and comparative embodiments in 650℃ saturated oxygen concentration lead-bismuth for 1000h are presented. The results show that Examples 1-4 have the thinnest oxide film and low grain boundary oxidation degree, indicating that the oxide film has the best protective properties, strong resistance to lead-bismuth corrosion, and strong resistance to grain boundary oxidation. Compared with the embodiments, Comparative Examples 1, 2, and 3 show that Al and Si have a positive effect on the oxide film protection and resistance to grain boundary oxidation. Compared with the embodiments, the reduced Ni and Cr content in Comparative Examples 1, 4, and 5 is detrimental to the formation of protective Cr and Al oxide films, leading to a decrease in the material's resistance to lead-bismuth corrosion and grain boundary oxidation corrosion, and an increase in the oxidation degree. A comparison of Examples 1-4 and Comparative Example 6 shows that doping with a reasonable amount (0~0.1%) of Y element has a positive effect on the material's resistance to grain boundary oxidation in high-temperature lead-bismuth corrosion environments.

[0050] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.

Claims

1. A method for preparing austenitic stainless steel resistant to lead-bismuth / supercritical carbon dioxide uniform corrosion and grain boundary oxidation, characterized in that: include, Prepare the following composition by mass fraction: 18% Ni, 14% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 3.5% Al, 0.08% Y, with the balance being Fe; Pure metal raw materials Fe, Cr, Ni, Nb, and Y are mixed in a vacuum induction furnace, placed in a crucible, and then smelted under vacuum and electricity. The smelting temperature is 1500℃, and the holding time is not less than 10 minutes. After the steel is liquefied and cleared, C and Al are added and fully melted before refining. After refining, 0.04 MPa argon gas is introduced into the induction furnace, and Si and Mn are added to further reduce the oxygen and sulfur content, and then it is cast into steel ingots; After smelting, the steel ingots are forged. During the forging process, the steel ingots are placed in a heating furnace and first heated to 800°C at a heating rate of 100°C / h for 1-2 hours. Then, they are heated to 1200°C at a heating rate of 100°C / h and held for 3 hours. After that, they are cooled to 1180°C and held for 1 hour before forging begins. The initial forging temperature is not lower than 1180°C and not higher than 1250°C, and the final forging temperature is 950-1000°C. The ingots are then air-cooled to obtain stainless steel forging billets, which are then polished to remove the oxide scale. The heat treatment process is as follows: the stainless steel forging billet is solution treated at 1150℃ for 60 minutes, water cooled, and then aged at 650℃ for 100 hours.

Citation Information

Patent Citations

  • High-temperature and corrosion resistant aluminum-containing austenitic stainless steel and preparation method

    CN113151747A

  • Aluminum-containing austenitic stainless steel resistant to liquid lead and bismuth corrosion and preparation method of aluminum-containing austenitic stainless steel

    CN115595511A

  • High-strength corrosion-resistant austenitic stainless steel for supercritical carbon dioxide environment and preparation method of high-strength corrosion-resistant austenitic stainless steel

    CN118345314A

  • A steel for a lead cooled reactor

    WO2016039679A1